2005
DOI: 10.1063/1.2035322
|View full text |Cite
|
Sign up to set email alerts
|

Faster H recovery in Pd nanoparticle layer based Gd switchable mirrors: Size-induced geometric and electronic effects

Abstract: Articles you may be interested inSize and alloying induced shift in core and valence bands of Pd-Ag and Pd-Cu nanoparticles Size and alloying induced changes in lattice constant, core, and valance band binding energy in Pd-Ag, Pd, and Ag nanoparticles: Effect of in-flight sintering temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Using XRD, Reddy and Reddy [158] measured w8% contraction of the lattice parameter of a 12.5 nm sized ZnMnTe nanosolid. GAXRD studies of the asdeposited Pd overlayer on the hydrogen-induced changes in the Gd switchable mirrors reveal a positive shift in the XRD peak position indicating lattice contraction with decrease in Pd nanoparticle size [159]. Extended XAFS investigation revealed that the CueCu distance in copper nanosolids with 0.7e1.5 nm mean diameter contracts with size in a D ÿ1 way and the CueCu dimer bond is reduced by 13% from 0.2555 to 0.221 nm of the 0.7 nm-sized particle [160].…”
Section: Observations and Interpretationsmentioning
confidence: 99%
“…Using XRD, Reddy and Reddy [158] measured w8% contraction of the lattice parameter of a 12.5 nm sized ZnMnTe nanosolid. GAXRD studies of the asdeposited Pd overlayer on the hydrogen-induced changes in the Gd switchable mirrors reveal a positive shift in the XRD peak position indicating lattice contraction with decrease in Pd nanoparticle size [159]. Extended XAFS investigation revealed that the CueCu distance in copper nanosolids with 0.7e1.5 nm mean diameter contracts with size in a D ÿ1 way and the CueCu dimer bond is reduced by 13% from 0.2555 to 0.221 nm of the 0.7 nm-sized particle [160].…”
Section: Observations and Interpretationsmentioning
confidence: 99%
“…10 Prior to deposition, the growth chamber has been evacuated to 1 ϫ 10 −6 Torr, and repeated argon purging was carried out to minimize the oxygen concentration in the growth chamber. High deposition pressure ͑10 −4 −10 −3 Torr of Ar͒, low substrate temperature ͑T s =30°C͒, and high flow rate of argon ͑FR= 20 SCCM͒ ͑SCCM denotes cubic centimeter per minute at STP͒ resulted in the formation of Pd nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…The Pd nanoparticles have shown better hydrogenation properties in comparison to their thin film and bulk counterparts. [10][11][12][13][14] The increased surface area and quantum confinement effects in the nanoparticles alter their electronic properties, resulting in enhanced activity and specificity of the catalysts. 15 The effect of alloying and size on the electronic properties of Pd can be clearly understood by synthesizing Pd-alloy nanoparticles with controlled dimensions.…”
Section: Introductionmentioning
confidence: 99%